Are Business Cycles Different in Asia and Latin America? - Hoffmaister, Willy (IMF Working Papers; Working Paper, 1997)
This paper compares business cycles in Asia and in Latin America using structural vector autoregression analysis with panel data. The evidence for countries in these regions suggests that (i) the main source of output fluctuations is supply shocks, even in the short run; (ii) the real exchange rate is driven mostly by fiscal shocks; and (iii) terms of trade shocks are important for trade balance fluctuations but not for output or real exchange rate fluctuations. However, in Latin America, as opposed to Asia, output is affected more by external and domestic demand shocks.